Preventing hepatitis C: what can positive injectors do? - Carruthers, Susan (Taylor and Francis Ltd, 2005)
The majority of hepatitis C prevention research among injectors is concerned with preventing initial exposure to the virus. Given that the prevalence of hepatitis C among injectors is between 50 and 60 per cent, one aim should be to prevent further transmission of the virus from infected to non-infected injectors. The major aim of this study was to investigate the risk management strategies hepatitis C positive injectors might take to prevent further transmission of the virus. A total of 111 hepatitis C positive injectors were recruited and interviewed with a questionnaire designed to gather information regarding current and past injecting behaviours and risk reduction options outlined in response to a series of injecting vignettes. The responses indicated that the majority of respondents recognised the risks associated with the various injecting scenarios and could describe actions by which they could reduce those risks. However, the examination of reported options revealed that while some of these would indeed eliminate the risk of further transmission others would be less effective because they either relied on unproven methods of removing viral material from used needle and syringes or the user assumed that other injectors had knowledge equivalent to that of the respondent.